Penerapan Metode Pembelajaran Kooperatif untuk Meningkatkan Hasil Belajar Matematika di Sekolah Dasar - Sinta Nur Izza; Muhammad Rakhma Diansyah (Pusat Riset dan Inovasi Nasional, 2021)
This research aims to analyze the application of cooperative learning methods and their impact on improving mathematics learning outcomes in elementary schools. The cooperative learning method is a pedagogical approach that involves cooperation between students in small groups to achieve joint learning goals. This research uses a quasi-experimental method with a non-equivalent control group design. The research sample consisted of fifth grade students in one of the elementary schools in City X, who were divided into an experimental group and a control group. The research results showed that students who studied using cooperative methods had significant improvements in mathematics learning outcomes compared to students who studied using conventional methods. Apart from that, this method also contributes to improving students' social skills and self-confidence. These findings indicate that the application of cooperative learning methods is not only effective in improving learning outcomes, but also in developing students' affective aspects. Therefore, this method is recommended to be applied more widely in mathematics learning in elementary schools..